MODEL PENYULUHAN HUKUM BERBASIS AGAMA DALAM MENCEGAH PRAKTIK PROSTITUSI DI KABUPATEN SUBANG - hamja, hamja; Supomo , Aris (Yustitia, 2017)
This study was carried out in Subang which has many places of prostitution. The objectives of the research are: (1) review the practices of prostitution phenomenon that occurs in Subang (2) assessing the implementation of legal counseling with religion basis in preventing the practices of prostitution (3) designing a legal counseling model based on religion in preventing practices of prostitution. The result of research has showed that there is an indication of religion lack of influence activity in the prostitution localization caused by several things: (1) the influence of religious activity in the prostitution localization is being ignored by the local community. (2) the lack of religion tolerance still occur in the brothel. (3) the lack of localization prostitution citizens on religious activities in mosques. (4) the conversion of prostitute still look forced, not because there is no intention to stop repeating the job.